Effective career development : advice for establishing an enjoyable career - Cook, Sarah (IT Governance Publishing, 2022)
The book includes exercises and activities to help you understand what is important to you in a job and how to attain your career goals. By reading this book, you'll be able to assess the advantages and disadvantages of different career paths and set clear career development goals.